Purinergic Signaling in the Pathophysiology and Treatment of Huntington’s Disease - Wiprich, Melissa Talita; Bonan, Carla Denise (Frontiers in Neuroscience, 2021)
Huntington’s disease (HD) is a devastating, progressive, and fatal neurodegenerative disorder inherited in an autosomal dominant manner. This condition is characterized by motor dysfunction (chorea in the early stage, followed by bradykinesia, dystonia, and motor incoordination in the late stage), psychiatric disturbance, and cognitive decline. The neuropathological hallmark of HD is the pronounced neuronal loss in the striatum (caudate nucleus and putamen). The striatum is related to the movement control, flexibility, motivation, and learning and the purinergic signaling has an important role in the control of these events. Purinergic signaling involves the actions of purine nucleotides and nucleosides through the activation of P2 and P1 receptors, respectively. Extracellular nucleotide and nucleoside-metabolizing enzymes control the levels of these messengers, modulating the purinergic signaling. The striatum has a high expression of adenosine A2A receptors, which are involved in the neurodegeneration observed in HD. The P2X7 and P2Y2 receptors may also play a role in the pathophysiology of HD. Interestingly, nucleotide and nucleoside levels may be altered in HD animal models and humans with HD. This review presents several studies describing the relationship between purinergic signaling and HD, as well as the use of purinoceptors as pharmacological targets and biomarkers for this neurodegenerative disorder.